2021
DOI: 10.1016/j.celrep.2021.108705
|View full text |Cite
|
Sign up to set email alerts
|

Predicting protein condensate formation using machine learning

Abstract: Highlights d An overview of amino acid features associated with condensate-forming (PPS) proteins d Development of a machine learning classifier (PSAP) to predict candidate PPS proteins d PSAP enabled the discovery of new PPS proteins, including DAZAP1 and CPEB3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 60 publications
2
91
1
Order By: Relevance
“…These differences indicate the importance of the liquid–liquid or liquid–solid phase separations of proteins. In addition, several methods have been developed to predict the PPS of proteins ( Vernon and Forman-Kay, 2019 ; Hardenberg et al, 2021 ; van Mierlo et al, 2021 ). These prediction methods can identify proteins with a high PPS from the proteome, such as the distribution of the amino acid residues and the complexity of the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…These differences indicate the importance of the liquid–liquid or liquid–solid phase separations of proteins. In addition, several methods have been developed to predict the PPS of proteins ( Vernon and Forman-Kay, 2019 ; Hardenberg et al, 2021 ; van Mierlo et al, 2021 ). These prediction methods can identify proteins with a high PPS from the proteome, such as the distribution of the amino acid residues and the complexity of the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…While both studies identified hundreds of candidate R-loop binding proteins (RLBPs) they overlapped by >100 proteins creating a higher confidence set of proteins that may preferentially recognize R-loops. Building on this set of high-confidence RLBPs it is possible to extract common protein features at the amino acid sequence level, and at a higher level such as protein domain organization or function (10)(11)(12). Based on this, here we use a random forest machine learning classifier to score R-loop binding potential for the human proteome.…”
Section: Introductionmentioning
confidence: 99%
“…We also analyzed PML isoforms for susceptibility to phase separation using the PSPredictor software package [ 53 ] based on machine learning algorithms. This analysis showed that the amino acid sequences of all the studied isoforms are characteristic of proteins capable of LLPS.…”
Section: Resultsmentioning
confidence: 99%
“…This tool enables the rapid generation of disorder profile plots for individual polypeptides as well as arrays of polypeptides. The prediction of LLPS PML-isoforms was performed using by PSPredictor software package [ 53 ].…”
Section: Methodsmentioning
confidence: 99%